Incidence of Age-Related Macular Degeneration in a Multi-Ethnic United States Population: The Multi-Ethnic Study of Atherosclerosis - Fisher, Diana E. (Ophthalmology, 2016)
OBJECTIVE: To describe the incidence of age-related macular degeneration (AMD) and associated risk factors in four racial/ethnic groups (white, black, Hispanic and Chinese) residing in the United States (U.S.). DESIGN: Prospective cohort study. PARTICIPANTS: 3811 participants, aged 46–86 years old, from the Multi-Ethnic Study of Atherosclerosis (MESA) cohort, with retinal data collected twice, on average, eight years apart. METHODS: Fundus images, taken using a digital camera through dark-adapted pupils using a standard protocol and the same equipment at both study visits, were graded centrally for early and late AMD based on drusen size, type and area, increased retinal pigment, retinal pigment epithelial depigmentation, neovascular lesions, and geographic atrophy using the modified Wisconsin Age-Related Maculopathy Grading System. Demographic, clinical, and laboratory measures were included in multivariable regression models to determine their impact on the variation in AMD incidence among racial/ethnic groups. MAIN OUTCOME MEASURES: Incident early and late AMD. RESULTS: The overall 8-year age- and sex-standardized incidence of early and late AMD was 4.1% and 2.3%, respectively, with incidence of early and late AMD highest in whites (5.3% and 4.1%), intermediate in Chinese (4.5% and 2.2%) and Hispanics (3.3% and 0.8%), and lowest in blacks (1.6% and 0.4%). Adjusting for age and sex, blacks had 70% lower risk of developing early AMD than whites and this decreased only slightly to 67% lower risk after multivariable adjustment. Adjusting for age, sex and race/ethnicity, hyperopia was associated with early AMD [Odds Ratio (OR)=1.51; 95% Confidence Interval (CI): 1.04–2.20], as was astigmatism [OR=1.47; 95% CI: 1.00–2.16], but not myopia (p=0.29). Age, race/ethnicity, current smoking, hyperopia, and AMD-susceptibility genotypes CFH RS1061170 and ARMS2 RS3793917 were independently associated with incident early AMD in multivariable models for the combined sample. However, the only statistically significant factor consistently associated with incident early AMD across the four racial/ethnic groups was increasing age. Risk factors for late AMD were not assessed due to its low incidence, particularly across racial/ethnic groups. CONCLUSION: Variation in the incidence of early AMD exists among racial/ethnic groups in the U.S. and is not explained by the clinical, genetic, and environmental factors included in this study.